Reaksi Pasar Modal Sebelum dan Sesudah Pengumuman Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) Darurat (Studi pada IDX-MES BUMN 17) - Arifah, Choirul; Muhfiatun, Muhfiatun (Universitas Islam Negeri Raden Intan, 2022)
This research is descriptive quantitative using an event study. This research aims to test and compare the IDX-MES BUMN 17 to the announcement of the emergency PPKM or community activity restriction on July 1, 2021 due to covid-19 pandemic situation. The sample as well as the population in this study used all of the companies listed in IDX-MES BUMN 17. The data analysis method used One-Sample Test and Wilcoxon Sign Rank Test. The daily test with One-sample Test showed that significant abnormal returns at t-9 and t-7. Meanwhile, a compared test with Wilcoxon Sign Rank Test showed that there were differences in abnormal return, security return variability, and trading volume activity before and after the implementation of Emergency Community Activity Restrictions (PPKM Darurat) but not significant on IDX-MES BUMN 17.